A numerical investigation into the aerodynamic effects of tubercles in wind turbine blades - Abate, Giada (Georgia Institute of Technology, 2019)
Wind turbine performance is clearly affected by complicated environmental effects such as atmospheric turbulence, ground boundary layer, and variation of free-stream wind direction and amplitude. Since the main goal of a wind turbine is energy production, the irregular nature of the wind is considered the main obstacle to a constant power output. Sinusoidal modifications (i.e., tubercles) placed on the leading edge of wind turbine blades seem to be a promising solution to this problem, since they generate vortices able to delay flow separation and improve the aerodynamic performance in the post-stall regime. The main objective of the present study is to give insights into the application of tubercles applied on the leading edge of wind turbine blades, specifically the NREL Phase VI wind turbine, such that performance enhancement can be achieved. Tubercles are sinusoidal bumps located at the leading edge of humpback whale flippers, which are able to improve flow attachment by acting like flow control devices similar to vortex generators. This discovery was the starting point for the development of several projects in the application of tubercles in different areas. In the present work, tubercles have been applied to the NREL Phase VI wind turbine blade to study their effects on blade aerodynamics and wind turbine performance. In particular, tubercle effects on shaft torque and annual energy production (AEP) have been analyzed; more specifically, tubercle amplitude, wavelength, and spanwise location have been considered as design variables. Moreover, since the physical phenomenon behind tubercles is still not fully clear, a physical analysis has been conducted to understand their working principles and to compare the new findings with previous works. Since past research on wind turbine application considers random values of tubercle geometric parameters (amplitude and wavelength), in the present work a more systematic study has been made by using a design of experiments (DoE) for the generation of tubercle ...